RANCANG BANGUN SISTEM KENDALI OTOMATIS KELEMBABAN TANAH DAN SUHU LINGKUNGAN PADA TANAMAN BERBASIS ARDUINO - Fikri; Rahmat Fauzi (Computer Science and Industrial Engineering, 2024)
The design of an automatic humidity and temperature control device in a plant environment using the Arduino Uno R3 system is designed to make it easier to take care of plants. Plants are a source of human life, especially in agriculture. Things that are still less of a concern when caring for plants are the lack of attention to the humidity and temperature of the environment in plants because it can have an impact on the soil that becomes dry or arid and can have an impact on plants to wither or even die. In carrying out plant care, it is done by only watering twice a day manually and can even forget to water and also not pay attention to the temperature in the plant environment. So that in doing maintenance is very less effective and efficient, because it takes a lot of time. Furthermore, in facilitating the process of plant care, without having to water manually or carry out treatment directly to the plant. So the soil moisture sensor is used to measure the level of soil moisture and the LM35 sensor which functions to read the temperature around the environment around the plant, after the measurement results will be displayed on the LCD. So this research examines how to design automatic control of humidity and temperature in plants.